How much does violence tax trade? - S. Brock Blomberg; Gregory D. Hess (Center for Economic Studies and ifo Institute (CESifo), 2004)
We investigate the empirical impact of violence as compared to other trade impediments on trade flows. Our analysis is based on a panel data set with annual observations on 177 countries from 1968 to 1999, which brings together information from the Rose [2004] dataset, the ITERATE dataset for terrorist events, and datasets of external and internal conflict. We explore these data with traditional and theoretical gravity models. We calculate that, for a given country year, the presence of terrorism, as well as internal and external conflict is equivalent to as much as a 30 percent tariff on trade. This is larger than estimated tariffequivalent costs of border and language barriers and tariff-equivalent reduction through GSPs and WTO participation.
Keywords: D74; E6; H5; H1; O11; 330; trade; conflict; terrosism; Gewalt; Politische Gewalt; Politischer Konflikt; Nichttarifäre Handelshemmnisse; Zolltarif; Außenwirtschaft; Schätzung; Welt